2022
DOI: 10.1111/and.14384
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricaemia is an important risk factor of the erectile dysfunction: A systematic review and meta‐analysis

Abstract: Serum uric acid can affect endothelial function, and hyperuricaemia‐induced endothelial dysfunction is involved in the pathogenesis of cardiovascular diseases. As endothelial dysfunction is also a main pathogenic mechanism of erectile dysfunction (ED), the present study aims to evaluate the relationship between hyperuricaemia and ED via systemic review and meta‐analysis. Five cohort studies and six cross‐sectional studies on hyperuricaemia and ED, including a total of 454,510 participants, were recruited. Odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Meanwhile, an Italian study found that elevated UA levels might even serve as a predictor of the severity of ED 28 . According to a recently published meta-analysis, urate-lowering treatment could reduce the risk of ED by 27% in patients with hyperuricemia 11 . Several cohort studies have shown that the incidence of ED in patients with gout was 1.21-2.04 fold higher compared to those with gout 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, an Italian study found that elevated UA levels might even serve as a predictor of the severity of ED 28 . According to a recently published meta-analysis, urate-lowering treatment could reduce the risk of ED by 27% in patients with hyperuricemia 11 . Several cohort studies have shown that the incidence of ED in patients with gout was 1.21-2.04 fold higher compared to those with gout 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia and gout have been demonstrated to induce endothelial dysfunction, which is the common pathogenesis of vascular ED 9,10 . Some cohort studies have demonstrated that ED incidence was signi cantly higher in patients with hyperuricemia or gout compared to those without hyperuricemia or gout 11,12 . Although considerable evidence supports the correlation of UA levels and gout in ED, the role of UA levels and gout in ED is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…5, after excluding each SNP, the overall error does not change much, indicating that the results are reliable. Multiple prior systematic reviews and meta-analyses have found that greater serum uric acid levels are related with the development of ED[8, 13,14]. Furthermore, clinical prediction model studies have demonstrated that serum UA can be used as a risk factor for ED [15].Furthermore, hyperuricemia may be regarded an independent risk factor in addition to known risk factors.…”
Section: Sensitivity Analysismentioning
confidence: 99%